2019
DOI: 10.12965/jer.1836532.266
|View full text |Cite
|
Sign up to set email alerts
|

Using stochastic resonance and strength training as part of a rehabilitation programme for recurrent low back pain treatment: a case study

Abstract: Low back pain (LBP) is a common disabling health problem that can cause decreased spine proprioception. Stochastic resonance (SR) can influence detection performance, besides improving patients with significant sensory deficits, but have not been thoroughly tested for LBP. This study aimed to examine the application of SR therapy (SRT) and strength training for LBP treatment. The subject was a resistance-trained male in his early thirties. His back pain was unbearable after a strength training session. Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that regular exercise helps to prevent pain (Sulejanov, 2009, Lizier et al, 2012, Washif et al, 2019 and it has been found that pain is worsened by Covid (Serrano-Ibáñez et al, 2021). Furthermore, as for the beneficial effect of isometric exercise on the body (Rio et al, 2017, Noorkõiv et al, 2015, Schott et al, 1995, this methodology differs in that it can be performed every day and in any place (gyms, medical centers, homes, and even at work).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that regular exercise helps to prevent pain (Sulejanov, 2009, Lizier et al, 2012, Washif et al, 2019 and it has been found that pain is worsened by Covid (Serrano-Ibáñez et al, 2021). Furthermore, as for the beneficial effect of isometric exercise on the body (Rio et al, 2017, Noorkõiv et al, 2015, Schott et al, 1995, this methodology differs in that it can be performed every day and in any place (gyms, medical centers, homes, and even at work).…”
Section: Discussionmentioning
confidence: 99%
“…However, other treatment options can be used, as studies show that regular exercise has been identified as a primary preventive and management of pain (Sulejanov, 2009, Lizier et al, 2012, Washif et al, 2019. It is considered that there is a strong connection between COVID and the worsening of the pain.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, SR-WBV was originally developed to increase performance of professional ski athletes. Nowadays it is used in different sports as injury prevention, but also in therapies with Parkinson patients ( 33 ), stroke patients ( 34 ), frail elderly ( 32 ), or patients with chronic low back pain ( 35 ). However, devices working with SR-WBV are big, heavy and expensive and thus rather used in physiotherapy or in fitness centers than at home.…”
Section: Introductionmentioning
confidence: 99%